Non-degrading CW UV generation in β-barium borate at 257 nm using an elliptical focusing enhancement cavity. (4th June 2019) - Kiefer, Daniel; Preißler, Daniel; Führer, Thorsten; Walther, Thomas
Abstract: With a combination of an elevated temperature for the β -barium borate (BBO) crystal and an elliptical focusing cavity we succeeded in eliminating the degradation in BBO during second harmonic generation into the ultraviolet (UV). We were capable of generating over 600 mW continuous-wave UV light at 257 nm with an off-the-shelf crystal for over 8 h without any sign of degradation. Our results indicate that the degradation is caused by color centers generated by two-photon absorption (TPA) strongly increasing the absorption of the fundamental radiation. While the higher crystal temperature reduces the TPA coefficient and the life time of the color centers, elliptical focusing strongly reduces the peak irradiance of the fundamental and thus its absorption.